INTERACTIVE MULTIMEDIA TO SUPPORT ENGLISH WRITING TASKS ACTIVITY AT HIGH SCHOOL - Agci Hikmawati (UNMUHBABEL Press, 2018)
This research is intended to develop writing tasks based on interactive multimedia using Adobe Flash CS3. The objectives of this research are to establish writing tasks based on suitable interactive multimedia for the tenth - grade students and to find out whether the design of interactive multimedia for the tenth - grade students is useful or not in teaching - learning process.This research type is research and development. The data were collected through questionnaires pre - test and post - test. The research procedure has the steps are as follows, the needs analysis phase concerns the collection of the data on the student's needs. The design phase deals with designing the interactive learning media. The development phase affects the development of the first draft of the interactive learning media, asking experts to judge and validate it. Validation involved two kinds of test, namely alpha and beta testing. Alpha testing involved material and content experts, and beta testing involved 19 students. The implementation phase deals with trying - out the interactive learning media in the class. The evaluation phase is where the interactive learning media evaluated through the feedback. Based on the data analysis, the research finding shows that the writing tasks based on interactive multimedia for the tenth-grade students are feasible. Feasibility of the interactive multimedia was very good. Percentage of assessment by the content expert reached 80.56%, the media expert 87% and the English teacher reached 85%, and based on the students' opinion reached 81%. The calculation of T - paired test showed that there was a difference in learning achievement between the pre-test and the post-test score 66.95 to 78.00 or 14.17%. It means that there is an increasing score and this interactive multimedia is effective.